Recent advances in the combination of capillary electrophoresis with mass spectrometry: from element to single-cell analysis - Klepárník, Karel (Electrophoresis, 2013)
This overview deals with the latest development of electrophoresis in capillaries and microfluidic devices coupled to MS detection. A wide selection of relevant articles covers the literature published from January 2010 till June 2012 as a continuation of the review article on the same topic by Pantuckova et al. [Electrophoresis 2011, 32, 43-51]. Special attention is paid to the new improvements in instrumentation and methodology of three interfacing methods, ESI, matrix-assisted desorption/ionization, and ICP. Representative examples illustrate applications in the proteomics, glycomics, metabolomics, biomarker research, forensics, pharmacology, food analysis and single-cell analysis. The combinations of MS with capillary versions of electrochromatography, ITP, IEF, and micellar electrokinetic chromatography are not included.
Keywords: analýza jednotlivých buněk; Microfluidic Analytical Techniques; Electrophoresis, Capillary; biologické markery; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Biomarkers; elektroforéza kapilární; Food Analysis; proteomika; mikrofluidní analytické techniky; hmotnostní spektrometrie; hmotnostní spektrometrie s elektrosprejovou ionizací; Proteomics; analýza potravin; Mass Spectrometry; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Drug Contamination; kontaminace léku; Single-Cell Analysis; Spectrometry, Mass, Electrospray Ionization